2018
DOI: 10.1016/j.molmet.2017.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Elevating adipose eosinophils in obese mice to physiologically normal levels does not rescue metabolic impairments

Abstract: ObjectiveObesity is a metabolic disorder that has reached epidemic proportions worldwide and leads to increased risk for diabetes, cardiovascular disease, asthma, certain cancers, and various other diseases. Obesity and its comorbidities are associated with impaired adipose tissue (AT) function. In the last decade, eosinophils have been identified as regulators of proper AT function. Our study aimed to determine whether normalizing the number of AT eosinophils in obese mice, to those of lean healthy mice, woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 29 publications
4
47
2
Order By: Relevance
“…Likewise, our own lab has published data showing that while WAT eosinophils increased with 48 hr cold exposure, fat pads with further increased eosinophils by rIL-5 treatment had no indication of increased beiging capacity [110]. In the same study we found that increased WAT eosinophils from rIL-5 treatment yielded no improvements in lipid & mixed-meal tolerance, insulin sensitivity, weight gain, metabolic rate, food intake & locomotion, or general inflammation ( Table 1).…”
Section: Downloaded Fromsupporting
confidence: 63%
See 1 more Smart Citation
“…Likewise, our own lab has published data showing that while WAT eosinophils increased with 48 hr cold exposure, fat pads with further increased eosinophils by rIL-5 treatment had no indication of increased beiging capacity [110]. In the same study we found that increased WAT eosinophils from rIL-5 treatment yielded no improvements in lipid & mixed-meal tolerance, insulin sensitivity, weight gain, metabolic rate, food intake & locomotion, or general inflammation ( Table 1).…”
Section: Downloaded Fromsupporting
confidence: 63%
“…It must be acknowledged however, that a parasitic infection most certainly modulates a number of other immune cells, and it is unknown how propolis influences other immune processes; for this reason, it is not possible to by guest, on www.jlr.org Downloaded from say the increased eosinophils are definitively responsible for the improved glucose tolerance in such models as they were non-specific modulations of eosinophils. In our own studies, we found that despite specifically elevating numbers of WAT eosinophils in obese mice with either recombinant IL-5 (rIL-5) treatment or using CCR2 deficient mice, there was no improvement in glucose tolerance [72,110,123]. Several studies have utilized IL-33 to increase ILC2s, eosinophils, and/or M2-like macrophages in WAT, often associated with weight loss and improved glucose control [31,94,106,112,115,117,119].…”
Section: Downloaded Frommentioning
confidence: 99%
“…Conversely, HFD in hyper‐eosinophilic IL‐5 transgenic mice causes eosinophil recruitment into the AT, M2‐like macrophages accumulation and prevention of IR . However, Bolus et al revealed that increasing the numbers of eosinophils in HFD‐fed mice using recombinant IL‐5 is not sufficient to improve obesity‐related metabolic dysfunctions . These conflicting results reveal that further studies are needed to clearly determine the precise role of eosinophils in the AT of obese animals.…”
Section: White Adipose Tissue (Wat) In Health and Obesitymentioning
confidence: 99%
“…), restoring AT eosinophils to physiological levels has not recapitulated such beneficial effects (Bolus et al. ). These mixed results demonstrate the need for continued research to determine the exact conditions that allow eosinophils to regulate AT homeostasis (i.e., which circumstances are permissive to eosinophil‐mediated improvements in metabolic health, and which are not).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies indicate eosinophils and innate lymphoid type 2 cells are key players in maintaining AT homeostasis, but these studies are not without their caveats (Bolus and Hasty 2018;Knights et al 2018). While high levels of systemically elevated eosinophils have been shown to protect against the effects of high-fat diet (HFD)-induced obesity (Wu et al 2011;Molofsky et al 2013;Hussaarts et al 2015), restoring AT eosinophils to physiological levels has not recapitulated such beneficial effects (Bolus et al 2017). These mixed results demonstrate the need for continued research to determine the exact conditions that allow eosinophils to regulate AT homeostasis (i.e., which circumstances are permissive to eosinophil-mediated improvements in metabolic health, and which are not).…”
Section: Introductionmentioning
confidence: 99%